The Pros and Cons of Agent Banking : Evidence from Senegal - Buri, Sinja; Cull, Robert; Giné, Xavier; Harten, Sven; Heitmann, Soren (World Bank, Washington, DC, 2018)
This study seeks to estimate the effects of access to agent banking on opening and usage of a savings account in urban and peri-urban areas in Senegal. A randomly selected group of individuals were given information about a savings account. Half of the individuals were encouraged to open the account at the nearest agent, while the other half were encouraged to do so at the closest branch. In addition, half of the individuals in each of these two groups were also given a monetary incentive to open the account. Study participants thus fall into one of five groups: (i) offered information about the account (Info), monetary incentives to open it (Incentives), and told to open it at the branch (Branch); ii) info, incentives and told to open it with an agent (Agent), (iii) info, no Incentives and branch (iv) info, no incentives and agent and (v) no info.